2017
DOI: 10.21307/ajon-2017-001
|View full text |Cite
|
Sign up to set email alerts
|

The complications of jejunostomy tubes for patients receiving Duodopa: New challenges for neuroscience nurses

Abstract: The use of Duodopa ® Levodopa-Carbidopa intestinal gel offers patients with advanced Parkinson’s disease (PD) an effective alternative therapy for the treatment of severe motor fluctuations and dyskinesia. This therapy requires the use of percutaneous endoscopic gastrostomy/jejunostomy tube (PEG/J) to deliver gel directly into the jejunum which poses new challenges for neuroscience nurses for the care and management of patients with PD. Due to the reported number of complications associated with PEG/J our faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Several other studies confirmed that JET-PEG individuals experience higher rates of repeated endoscopies. Sücüllü Karada g et al [40] published a 36.4% incidence of technical complications, half of them requiring repeated gastroscopies [41,42]. Blaise et al [43] reported the need for repeated endoscopies in up to 68% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies confirmed that JET-PEG individuals experience higher rates of repeated endoscopies. Sücüllü Karada g et al [40] published a 36.4% incidence of technical complications, half of them requiring repeated gastroscopies [41,42]. Blaise et al [43] reported the need for repeated endoscopies in up to 68% of patients.…”
Section: Discussionmentioning
confidence: 99%